2016
DOI: 10.1200/jop.2015.005538
|View full text |Cite
|
Sign up to set email alerts
|

Lower Patient Ratings of Physician Communication Are Associated With Unmet Need for Symptom Management in Patients With Lung and Colorectal Cancer

Abstract: BACKGROUND AND QUESTION ASKED:In this study, we assessed the prevalence of patientreported unmet needs for management of common cancer symptoms (pain, fatigue, depression, nausea/vomiting, cough, dyspnea, diarrhea) in a population-based sample of patients newly diagnosed with lung and colorectal cancer. How are unmet needs for symptom management in patients with lung and colorectal cancer associated with patient-rated physician communication quality?SUMMARY ANSWER: Fifteen percent of patients newly diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 33 publications
3
31
0
Order By: Relevance
“…Help with fatigue/lack of energy (23-32%) (Anderson et al, 2013;Browne et al, 2011;Northouse et al, 1999;Taylor et al, 2012;Walling et al, 2016) post-op (12-27%) (Carlsson et al, 2010;Harrison et al, 2011;Macvean et al, 2007;Santin et al, 2015) 70%; 44%-90% 67%; 46%-73%…”
Section: Physical/cognitivementioning
confidence: 99%
See 2 more Smart Citations
“…Help with fatigue/lack of energy (23-32%) (Anderson et al, 2013;Browne et al, 2011;Northouse et al, 1999;Taylor et al, 2012;Walling et al, 2016) post-op (12-27%) (Carlsson et al, 2010;Harrison et al, 2011;Macvean et al, 2007;Santin et al, 2015) 70%; 44%-90% 67%; 46%-73%…”
Section: Physical/cognitivementioning
confidence: 99%
“…More information about the risk of recurrence (46-63%) (Beckjord et al, 2008;Boudioni et al, 2001;Papagrigoriadis and Heyman, 2003;Salz et al, 2014;Sanoff et al, 2010) and/or symptoms of disease recurrence (89%) (Beckjord et al, 2008;Knowles et al, 1999;Lithner et al, 2015) 81%; 64%-95% 85%; 65%-95% 9 Information/education More information about the short-term and long-term effects of treatment on quality of life (40-78%) (Boudioni et al, 2001;Galloway and Graydon, 1996;Harrison et al, 2011;Kidd, 2014;Knowles et al, 1999;Morrison et al, 2012;Rozmovits et al, 2004;Sanoff et al, 2010) 83%; 73%-90% Health system/patientclinician communication On-going communication/contact with and support from a trustworthy clinician (16-56%) (Jefford et al, 2011;Lam et al, 2016;Li et al, 2012;Lithner et al, 2015Lithner et al, , 2012Rozmovits et al, 2004;Santin et al, 2015;Shun et al, 2014) 86%; 61%-95% Physical/cognitive Help with pain (abdominal) (23-28%) (Anderson et al, 2013;Browne et al, 2011;Di Fabio et al, 2008;Northouse et al, 1999;Taylor et al, 2012;Walling et al, 2016) post-op associated with adhesions/infected wounds/non-healing wounds (Browne et al, 2011;Carlsson et al, 2010;Harrison et al, 2011) 70%; 44%-90% 73%; 73%-90% Information/education More information about the exact diagnosis and what it means (52-80%) (Andersson et al, 2010;Baravelli et al, 2009;Boudioni et al, 2001;…”
Section: Information/educationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a recent study found that patient-rated physician communication quality was positively associated with patient-rated symptom management quality, with patients rating their physician’s communication highly being more likely to report having their symptom management needs met, compared to those with lower communication scores. 6 Prior studies have also shown that patient-provider interactions differ based on race/ethnicity. Specifically, racial/ethnic minority patients, particularly Asian and black patients, tend to report suboptimal communication with providers, and more discrimination by providers.…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in patient health outcomes have also been reported including improved symptom resolution, physical functioning, physiological status (e.g., blood pressure, HbA1c) and pain (Stewart, 1995). Studies specifically focused on cancer patients have shown similar impact on patient’s treatment participation (Street & Voigt, 1997), self-management behaviors (Walling et al, 2016) and physical and emotional health outcomes (Lake et al, 2014). Despite the importance of patient-provider communication, cancer patients’ communication needs often go unmet (Bruinessen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%